Seedling Functional Types and Cotyledons Shape Some Species of Woody Plant - Tri Handayani (Universitas Wiralodra, 2021)
ABSTRACT Woody plant produce small to large seeds which can affect germination process. Cotyledons as an important food source for early growth of seedlings. The position, function, and type of cotyledons when seeds germinate varies. This research aimed to determine cotyledons characters of woody plant seedlings collection in Bogor Botanic Gardens. The position, function and type of cotyledons were observed for 65 species of seedlings.This research used an observative method and was analyzed descriptively.The position of cotyledons when the seeds germinate are epigeal (above the ground) and hypogeal (remain in the soil). The epigeal cotyledons type found in 44 species that is higher than hypogeal cotyledons type (21 species). The function of cotyledons for seedlings is to reserve food or photosynthesis. Species with cotyledon reserve type were more than foliar cotyledons type (43 species and 22 species, respectively). The proportion of seedling types CER (cryptocotylar-epigeal-reservoir), CHR (cryptocotylar-hypogeal-reservoir), PEF (phanerocotylar-epigeal-foliaceous), PER (phanerocotylar-epigeal-reservoir), PHR (phanerocotylar-hypogeal-reservoir) were 3.08%, 16.92%, 33,85%, 29,23%, 16,92%, respectively.